Clinical efficacy of once-daily micronized purified flavonoid fraction 1000 mg tablet in patients with symptomatic chronic venous disease. (4th March 2019) - Kirienko, A.; Radak, D.; Maggioli, A.
Abstract: Aim: To investigate the clinical efficacy of micronized purified flavonoid fraction (MPFF) 1000 mg given as a single 1000 mg tablet once daily in patients suffering from chronic venous disease (CVD) vs MPFF 500 mg twice daily. Methods: In an international, randomized, double-blind, parallel-group study, patients classified C0s to C4 according to Clinical Etiological Anatomic Pathophysiologic [CEAP] classification and with leg pain graded as superior to 4 cm on a 10-cm visual analog scale (VAS), were treated for 8 weeks with either MPFF 1000 mg once daily or MPFF 500 mg twice daily. The present post-hoc analysis focuses on the effect of treatment over time in patients randomized to the MPFF 1000 mg group. Leg pain was assessed at each follow-up visit by VAS. VAS scores over time were compared between each visit using paired Student t -tests. Results: In total, 87 patients out of 174 were randomized to the MPFF 1000 mg group. Mean age ± SD was 49.1 ± 12.2 years, most of the patients were female (81.6%), the main CEAP classes of the most affected leg were C1 (20.7%), C2 (39.1%), C3 (33.33%), and the mean duration of CVD was 14.6 ± 10.9 years. Patients with previous CVD treatment represent 27.6% of the patients. A MPFF 1000 mg tablet once daily was associated with a significant and continuous reduction in leg pain throughout the treatment period: –1.54 cm (±1.45) from baseline to week 2 ( p  < .01), –1.11 cm (±1.06) from week 2 to week 4 ( p  < .01), –1.57 cm (±1.05) from week 4 to week 8 ( p  < .01). Conclusions: The new MPFF 1000 mg dose regimen in once daily tablets was associated with a rapid and continuous reduction in leg pain throughout the 8-week treatment period.